ANALISA KINERJA KEUANGAN DALAM PENINGKATAN LABA PADA PT. JASA RAHARJA (PERSERO) - Syane Amelia Sepang; Frendy Pelleng; Dolina Tampi (Universitas Sam Ratulangi, 2014)
The most important thing for the company to determines financial performance in the matter of financial report is to acknowledge the outcome of financial performance in order to compete in the economic development to maintain study performance of the company. In order to evaluate the performance, the calculation using profitability ratio and achieves Gross Profit Margin Net Profit Margin every year advance, because every year income experience increase. The analysis score over Return on Asset/ Return on Investment instability, because to the increase in profit in the third year is not to large compared with the previous year. For Return on Equity decreased, because income earned each year not by the equity every year, because despite rising profit, rising equity is greater than the profit. On the Profit Margin and Economical Rentability has increased, as earnings before interest and taxes in the financial statements in the financial statements on income (loss) from operations increased, and that the company’s revenue underwriting income indicates that the increase is happening and therefore contributes to the increase in Profit Margin and Economical Rentability every year. And the outcome of above analysis can be sean on PT. Jasa Raharja (Persero) financial performance can be said well achieved, because there are fluctuation in every year. Dispite on the RoA and RoE having a bit of downside, and the company has to increase RoA and RoE in order for having eficienly increasment. However the overall company financial performance having a well forward achievement every year with the increasment of company profit. Key Word : ( Financial Performance, Profitability